Current Research Status of Digital Technology in the Rehabilitation of Rare Neurological and Muscular Diseases - GUO Yixuan; GAO Yi; YAO Yiyang; QIN Zhuoyue; ZHANG Yaofang; JING Jiaqi; XIE Jing; GUO Jian; ZHANG Shuyang (罕见病研究)
ObjectiveTo review the randomized controlled trials (RCTs) at home and abroad on digital intelligence (DI)-driven rehabilitation in patients of neuromuscular disease, compare the effects of DI-driven rehabilitation with traditional rehabilitation, summarize the special needs and challenges faced by patients in rehabilitation of rare neuromuscular diseases, and provide evidence for the development and quality improvement of rehabilitation for rare neuromuscular diseases.MethodsWe searched PubMed, Web of Science, Embase, CNKI, VIP, and Wanfang databases for literature on neuromuscular diseases, rare diseases, digital and intelligent technologies, and rehabilitation published from the inception of the databases to June 2024. Basic and research-related information from the retrieved literature was extracted and analyzed.ResultsA total of 43 RCTs in English from 14 countries were included. The most studied diseases were Parkinson′s disease and multiple sclerosis. The application of DI-driven technologies in rehabilitation of rare neuromuscular diseases was still limited. The commonly used technologies were virtual reality (VR) games, intelligent treadmill assistance, gait training robots, hybrid assistive limb (HAL), wearable sensors and tele-rehabilitation (TR) systems. These technologies were applied in patients′ homes or rehabilitation service centers. The VR games significantly improved both static/dynamic balance functions and cognitive functions. The intelligent treadmill assistance significantly enhanced gait speed and stride length. The gait training robots significantly improved balance, gait speed and stride length of patients. The wearable exoskeletons significantly enhanced walking ability.ConclusionsDI-driven rehabilitation measures have great value and potential in the field of neuromuscular disease rehabilitation. Their advantages and characteristics can meet the diverse needs of rare disease patients. In the future, a hierarchical and collaborative rehabilitation service system should be established to meet the urgent needs of the rehabilitation of rare neuromuscular diseases. Combining the advantages of digitization and intelligence will provide standardized, scientific, convenient and affordable rehabilitation services to patients.